2013
DOI: 10.1017/s1431927613013810
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analyses Show Synergetic Effects of Biomechanical and Biochemical Stimulation on Mesenchymal Stem Cell Differentiation into Early Phase Osteoblasts

Abstract: We investigated the structural complexity and texture of the cytoskeleton and nucleus in human mesenchymal stem cells during early phase differentiation into osteoblasts according to the differentiation-induction method: mechanical and/or chemical stimuli. For this, fractal dimension and a number of parameters utilizing the gray-level co-occurrence matrix (GLCM) were calculated based on single-cell images after confirmation of differentiation by immunofluorescence staining. The F-actin and nuclear fractal dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…FD is already used as a diagnostic tool in many fields of research, including studies of; neurons (Ristanovic´ et al, 2014); retinal vasculature (Mendonca et al); bronchial tree (Gupta et al, 2014); tissue blood perfusion (Michallek & Dewey 2014); diagnosis of hepatocellular carcinoma (Lee et al); degree of differentiation of osteoblasts (Park et al, 2014) and degree of myocardial cellular rejection after heart transplantation (Moreira et al), among others. However; despite being a technique with good applicability for histological analysis, no research was found in the scientific literature assessing injured skeletal muscle tissue using fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…FD is already used as a diagnostic tool in many fields of research, including studies of; neurons (Ristanovic´ et al, 2014); retinal vasculature (Mendonca et al); bronchial tree (Gupta et al, 2014); tissue blood perfusion (Michallek & Dewey 2014); diagnosis of hepatocellular carcinoma (Lee et al); degree of differentiation of osteoblasts (Park et al, 2014) and degree of myocardial cellular rejection after heart transplantation (Moreira et al), among others. However; despite being a technique with good applicability for histological analysis, no research was found in the scientific literature assessing injured skeletal muscle tissue using fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of these methods in future studies can be directed to discriminate stem cells from different passages, to study the effects of different factors on the nuclear complexity of various cell lines or as tool for detecting stem cell differentiation. Although still in the early phase of application, several studies have recently used fractal and GLCM texture analysis for the similar purpose [21,46]. If future studies confirm the validity of these methods, a possible next step in the process of application could be a development of automated software, which would be able to calculate fractal and GLCM texture parameters in real time, without previous image processing.…”
Section: Resultsmentioning
confidence: 99%
“…New methods and modifications of fractal analysis are also being discovered [19], thus allowing this mathematical method to be applied in different areas of natural sciences. Unlike fractal analysis, gray level co-occurrence matrix (GLCM) texture analysis can be used in biomedical research to analyze texture features of histological images and also to quantify structural changes in cells and tissues [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…GLCM texture analysis is another mathematical method. While FD is a parameter of structural complexity, GLCM parameters are used to detect changes in the texture features of histological specimens (Yogesan et al, 1998; Park et al, 2014). Actually, these parameters contain information about the positions of pixels which have similar gray level values.…”
Section: Discussionmentioning
confidence: 99%